COP 26—Examining the balance between ambitious pledges and realistic expectations - Bassam Fattouh; James Henderson (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2021)
COP26, which is to be held in Glasgow in the first two weeks of November, is set to be a defining moment in global climate negotiations as almost 200 countries come together to review their environmental performance since 2015 and to set new emissions targets for 2030. In this special edition of the Oxford Energy Forum we have gathered the thoughts of many leading researchers in the field of energy and the environment to review both the overall expectations for the COP and the challenges which are likely to be faced in reaching global agreement on a series of very complex issues. We have also gathered views from a number of the key countries involved in the negotiations, including major energy exporters and importers, in order to provide a variety of different perspectives on the negotiations. Articles on China, India, Japan, Saudi Arabia, Russia the EU and Brazil, as well as thoughts from the UK, which holds the presidency of COP26, underline the broad range of bargaining positions that will be taken into this vital meeting, while the Forum also provides insights into a number of key issues that are likely to feature in the negotiations such as climate justice, the role of net zero targets, the potential of CCUS and the role of nuclear power in the energy transition.
Keywords: 330